Reduction of E. coli O157: H7 and Bacillus cereus levels in red pepper powder using dielectric barrier discharge (DBD) plasma for enhanced quality. (March 2022) - Kim, Yeon Ho; Lee, Chanjae; Lee, Sung-Jae; Yoon, Ki Sun
Abstract: Although irradiation has been used to destroy bacteria and molds in spices globally, a new technology is needed to alleviate public fears of irradiation, the high cost of irradiated food, and environmental contamination at the irradiation facility. The objective of this study was to investigate the effects of dielectric barrier discharge (DBD) plasma on Eshcericah coli O157: H7 and Bacillus cereus levels in red pepper powder and the physicochemical properties of red pepper powder stored at 25 °C. RNA expression was determined by qRT-PCR. The surface of bacteria treated with DBD plasma was observed with a Field Emission Scanning Electron Microscope (FE-SEM). Red pepper powder (5 g) inoculated with E. coli O157: H7 and B. cereus was treated with DBD plasma using argon as a plasma-forming gas at 31 kW for 0, 5, 10, and 15 min. DBD plasma did not significantly decrease the bacterial concentrations with an increase in treatment time. However, DBD plasma treatment for 15 min killed E. coli O157: H7 more rapidly during storage. Expression of virulence genes of both E. coli O157: H7 and B. cereus was decreased by DBD plasma treatment for 15 min. Results of FE-SEM showed that DBD plasma damaged the bacterial cell membranes, leading to cell death. Physiochemical properties of red pepper powder were not changed for one month after treatment with DBD plasma. Thus, DBD plasma treatment for 15 min is recommended to control foodborne pathogens in red pepper powder without changing its physicochemical properties. Highlights: Dielectric barrier discharge (DBD) plasma can enhance the quality of red pepper powder. Effect of DBD plasma was more effective on E. coli O157: H7 than on B. cereus . Expression levels of virulence genes of E. coli O157: H7 and B. cereus were decreased. The morphological change of pathogens and red pepper powder were examined.